A cross-sectional study to explore the relationship between the technology acceptance model and burnout and depression among pharmacists working with a pharmacy robotic dispensing system - Alshamsi, Amna Ibrahim; AlHarthi, Mariam; AbdulQader, Hessa; Chhabrani, Pramod; Ahmed, Safa; Almansoori, Muna (Frontiers in Psychology, 2025)
ObjectivesThis study compares hospitals using a pharmacy robotic dispensing system (RPDS) with those using manual dispensing systems regarding burnout and depression among pharmacists in Emirates Health Services (EHS) hospitals. Furthermore, this study aims to bridge the gap in the literature concerning the relationship between burnout and the technology acceptance model (TAM).MethodsA cross-sectional survey was conducted to determine whether burnout and TAM differed between hospitals with RPDS and those with manual dispensing system. The study was carried out in ten hospitals governed by the EHS.ResultsA total of 256 respondents completed the survey. Burnout and depression levels among pharmacists working with RPDS did not differ significantly from those using manual dispensing systems. However, the median of personal burnout levels in female pharmacists (Mdn = 50) differed significantly from those using manual dispensing systems (Mdn = 25; U = 3497.5, z = −7.8, p < 0.001, r = −0.49). In contrast, male pharmacists exhibited higher levels of technology acceptance (U = 11,357, z = 5.58, p < 0.001, r = 0.35; U = 10,391, z = 4.0, p < 0.001, r = 0.25).ConclusionThis study explored the differences in burnout, depression levels, and TAM among employees working in public hospitals in the United Arab of Emirates. Overall, automation had both positive and negative effects on workplace stressors experienced by pharmacy staff.